The Management of Mask Waste and Its Problems at the Faculty of Public Health, Nusa Cendana University - Roga, Anderias Umbu; Tapo, Konstantinus Firminus; Sir, Amelya B (Preventif : Jurnal Kesehatan Masyarakat, 2025)
The increased use of masks has led to a new problem, namely the rise in the amount of mask waste, which has the potential to become a medium for virus transmission if not properly managed. Therefore, proper management of mask waste is necessary to reduce the amount of waste and minimize the spread of COVID-19 through used masks. The purpose of this study is to describe the mask waste management practices among students of the Faculty of Public Health at Nusa Cendana University. This is a quantitative descriptive study conducted using a survey method. The population in this study consists of active students of the Faculty of Public Health at Nusa Cendana University, with a total sample of 322 respondents selected using the proportionate stratified random sampling technique. Data were collected using a questionnaire. The data analysis used was univariate analysis, which only looks at the frequency distribution of each variable studied. The results showed that 51.9% of respondents demonstrated good mask waste management practices, as indicated by proper actions in collecting, sorting, disinfecting, altering the form, disposing of the waste, and washing hands after handling used masks. Students with good knowledge and positive attitudes were more likely to practice proper mask waste management. A total of 91.9% of students had good knowledge, and 86.3% had positive attitudes. It is recommended that the Faculty of Public Health at Nusa Cendana University provide special waste bins specifically for mask waste.